Evaluation of Learners’ Satisfaction with Open Flexible and Distance Learning Services at the University of Lagos Distance Learning Institute - Adenike Oladipo; Esther O. Oladele; Oladipupo Ajeyalemi; Folashade Afolabi; Peter O. Olayiwola; Johnson A. Adewara; Andrew Akala; Uchenna Udeani (West African Journal of Open and Flexible Learning, 2024)
The prospects of Open and Distance Learning (ODL) as the best way to acquire formal education, especially having to work and learn simultaneously have led to curiosity in investigating the challenges that come with this great opportunity. This study evaluated learners’ satisfaction with the services provided by the Distance Learning Institute (DLI), University of Lagos, at various levels of learners’ engagement. A survey research design using non-probability quota sampling was adopted. Data was collected using a structured questionnaire which was developed and validated for testing learner satisfaction in ODL at the University of Lagos. A sample size of 3,724 learners was used for the study. Descriptive statistics such as frequencies, percentages, mean and standard deviation were used in analysing the data. Findings from this study revealed that DLI has been generally successful in satisfying learners at the pre-enrolment, process and product stages with mean response ratings of 7.27, 5.63, and 6.87 respectively. However, the learners were dissatisfied with the adequacy of course materials with a mean of 4.49 and radio lectures with a mean of 4.26. Furthermore, DLI graduates are slightly satisfied with the programme completion process such as result processing and convocation with mean response ratings of 7.74 and 7.44 but dissatisfied with the restrooms of mean 5.02. It is suggested that the administrators of DLI should adopt a continuous improvement approach, focusing on specific areas of the educational journey where satisfaction levels are low such as course materials, radio lectures, restrooms and related services to enhance graduate satisfaction.